2001
DOI: 10.2519/jospt.2001.31.12.741
|View full text |Cite
|
Sign up to set email alerts
|

Control of Acceleration During Sudden Ankle Supination in People With Unstable Ankles

Abstract: Study Design:Comparative study of differences in functional control during ankle supination in the standing position in matched stable and unstable ankles (ex post facto design). Objectives: To document acceleration and deceleration during ankle supination in the standing position and to determine differences in control of supination perturbation between stable and unstable ankles. Background: Repetitive ankle sprain can be explained by mechanical instability only in a minority of cases. Exercise therapy for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 41 publications
2
53
0
4
Order By: Relevance
“…Former conducted studies showed that alteration during gait initiation (GI) and landing followed ankle instability, which further supported central alteration or open-loop neuromuscular control alteration in patients with CAI (10,11). On the other hand, previous studies suggested proprioceptive deficits (12) and peroneal muscles reaction time delay in response to unexpected perturbation, which showed deficit in closed-loop neuromuscular control, in patients with CAI (13); however, some contradictory studies showed no difference in peroneal muscles reaction time between patients with ankle instability and healthy individuals (14,15). Gutierrez et al, (9) suggested that closed-loop control may have no important role in maintaining the stability of ankle during perturbation (9).…”
Section: Introductionmentioning
confidence: 82%
“…Former conducted studies showed that alteration during gait initiation (GI) and landing followed ankle instability, which further supported central alteration or open-loop neuromuscular control alteration in patients with CAI (10,11). On the other hand, previous studies suggested proprioceptive deficits (12) and peroneal muscles reaction time delay in response to unexpected perturbation, which showed deficit in closed-loop neuromuscular control, in patients with CAI (13); however, some contradictory studies showed no difference in peroneal muscles reaction time between patients with ankle instability and healthy individuals (14,15). Gutierrez et al, (9) suggested that closed-loop control may have no important role in maintaining the stability of ankle during perturbation (9).…”
Section: Introductionmentioning
confidence: 82%
“…7 The phenomenon of acceleration has been investigated through methodologies such as trapdoor experiments and electromyography. [8][9][10] However, isokinetic analysis is an assessment method that is more dynamic 11 and shows a behavior that is closer to the functionality of the sport.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Other studies, however, showed a significant difference in evertor muscles latency time when comparing stable and unstable ankles during inversion movement of 30°. 22,24,26,30,37,45 Evertor muscles of unstable ankles were shown to have a longer latency time and the latency time of the fibularis longus and brevis muscles increased with plantar flexion. 32,37 Obviously, these conflicting results require further research with different methods.…”
mentioning
confidence: 99%
“…Consequently, neuromuscular dysfunction is seen as an important factor in the etiology of CAI. 14,[22][23][24][25][26]30,37,45 Most published studies on reaction time 9,11,18,19,24,26,30,36,45 are based on trapdoor experiments, measuring surface electromyography (EMG) response of lower leg muscles. To assess muscle recruitment, latency time (defined as the time between disturbance of the equilibrium and the first EMG signal) is often used as the outcome measure.…”
mentioning
confidence: 99%
See 1 more Smart Citation